Phloem-specific expression of Yang cycle genes and identification of novel Yang cycle enzymes in Plantago and Arabidopsis. - Pommerrenig, Benjamin; Feussner, Kirstin; Zierer, Wolfgang; Rabinovych, Valentyna; Klebl, Franz; Feussner, Ivo; Sauer, Norbert (The Plant Cell, 2011)
The 5-methylthioadenosine (MTA) or Yang cycle is a set of reactions that recycle MTA to Met. In plants, MTA is a byproduct of polyamine, ethylene, and nicotianamine biosynthesis. Vascular transcriptome analyses revealed phloem-specific expression of the Yang cycle gene 5-METHYLTHIORIBOSE KINASE1 (MTK1) in Plantago major and Arabidopsis thaliana. As Arabidopsis has only a single MTK gene, we hypothesized that the expression of other Yang cycle genes might also be vascular specific. Reporter gene studies and quantitative analyses of mRNA levels for all Yang cycle genes confirmed this hypothesis for Arabidopsis and Plantago. This includes the Yang cycle genes 5-METHYLTHIORIBOSE-1-PHOSPHATE ISOMERASE1 and DEHYDRATASE-ENOLASE-PHOSPHATASE-COMPLEX1. We show that these two enzymes are sufficient for the conversion of methylthioribose-1-phosphate to 1,2-dihydroxy-3-keto-5-methylthiopentene. In bacteria, fungi, and animals, the same conversion is catalyzed in three to four separate enzymatic steps. Furthermore, comparative analyses of vascular and nonvascular metabolites identified Met, S-adenosyl Met, and MTA preferentially or almost exclusively in the vascular tissue. Our data represent a comprehensive characterization of the Yang cycle in higher plants and demonstrate that the Yang cycle works primarily in the vasculature. Finally, expression analyses of polyamine biosynthetic genes suggest that the Yang cycle in leaves recycles MTA derived primarily from polyamine biosynthesis.